Kajian Numerik Pengaruh Geometri Intake Pompa dan Anti-Vortex Device Terhadap Aliran Pada Intake Pompa - Sianipar, Junifer Hotma Parulian (Universitas Muhammadiyah Metro, 2024)
Errors in pump intake design are often caused by incorrect geometry, inadequate immersion, and uneven velocity distribution, which cause vibration, noise, reduced discharge, head, and pump efficiency. This study aims to: 1) study the effect of variable pump bay widths of 3 meters, 4 meters, and 5 meters on fluid flow at the pump intake. 2) Study the effect of variable pump bay widths of 3 meters, 4 meters, and 5 meters with anti-vortex devices on fluid flow at the pump intake. This research method uses computational fluid dynamics (CFD) with a tetrahedral mesh because of the complex shape and geometry of the pump intake. The k-ε realizable turbulence model is used to analyze the flow that produces vortices. The results of the study show that based on the variable pump bay width, the average velocity distribution entering the pump bay is still in accordance with the recommended standard, which is below 0.5 m/s. The pump bay with a width of 3 meters has the highest average velocity compared to other pump bays. Based on the variable pump bay width and the use of anti-vortex devices, it is concluded that the pump intake design with anti-vortex devices has a more uniform flow distribution. However, in a pump bay with a width of 3 meters, even though an anti-vortex device is used, the flow distribution remains non-uniform because the geometric width of 3 meters is not sufficient